Association between uterine leiomyoma and metabolic syndrome in parous premenopausal women: A case–control study. Issue 46 (November 2016) - Tak, Young Jin; Lee, Sang Yeoup; Park, Sun Ki; Kim, Yun Jin; Lee, Jeong Gyu; Jeong, Dong Wook; Kim, Seung Chul; Kim, In Joo; Yi, Yu Hyun
Abstract : Abstract: Previous studies have reported that uterine leiomyoma (UL) may share pathogenic features with obesity and hypertension, which are components of metabolic syndrome (MetS). We examined the association between UL and MetS in premenopausal parous women. This 1:1 case–control study was conducted on 615 asymptomatic women with UL and 615 women without UL that were matched for age, reproductive history, and hormonal use, who underwent a comprehensive health examination. UL was diagnosed by a gynecologist based on transvaginal ultrasonography findings. Blood pressure (BP), body composition, fasting plasma glucose, lipid profiles, insulin, and HOMA-IR were checked. Median age of the 1230 study subjects was 44 (40–47) years and 7% had MetS. Women with UL had significantly higher waist circumferences and body fat, BP, and low-density lipoprotein cholesterol (LDL-C) than women without UL. Although nonsignificant, the prevalence of MetS was higher in the UL group than in the non-UL group (9.3% vs 5.7%). In addition, the prevalence of UL increased as the number of abnormal metabolic components increased and was higher than in women without UL. Conditional logistic regression analysis, after adjustment for confounding factors, showed that hyperglycemia was significantly associated with an increased risk of UL (odds ratio = 1.45; 95% confidence interval, 1.10–1.89). Prevalence of abnormal metabolic component was higher in premenopausal women with UL than in normal controls, regardless of age or reproductive history. Furthermore, the study suggests that UL may share pathogenic features with the components of MetS and that women with UL be considered eligible for the early screening of metabolic abnormalities.